Actuator fault tolerance evaluation approach of nonlinear model predictive control systems using viability theory - Ghaniee Zarch, Majid; Puig, Vicenç; Poshtan, Javad; Shoorehdeli, Mahdi Aliyari (Journal of process control, 2018)
•Propose an approach to evaluate the actuator fault tolerance.•A nonlinear model predictive control (NMPC) system is considered.•The system is represented in a linear parameter varying (LPV) form.•Viability theory concepts in a set form (viability kernel, capture basin) is used.•Assess if after the fault the NMPC controller will be able to achieve their goal.•An algorithm is developed to assess the tolerance of the NMPC controller.•Two application examples (pasteurization plant, mobile robot) are used. In this paper, an approach to evaluate the actuator fault tolerance of a nonlinear model predictive control (NMPC) system using viability theory is proposed. Viability theory provides several concepts formulated in a set form (viability kernel and capture basin) that are very useful to assess if after the fault the NMPC controller will be able to achieve their goal either using a reconfiguration or an accommodation strategy. By representing the nonlinear model of the system in a linear parameter varying (LPV) form and using zonotopes to evaluate viability sets, an algorithm is developed and implemented that is able to assess the tolerance of the NMPC controller. To illustrate the proposed approach two application examples based on well-known control problems (a pasteurization plant and a mobile robot) are used.